Strengthening Transformational Leadership Based on Local Wisdom in Supporting Digital Transformation in Pesanggrahan Village, Mojokerto Regency - Mi'rojul Huda; Muhammad Farid Ilhamuddin; Muhammad Nuril Mukminin; Moh. Najmuddin; Esa.P.B.G.G Patridina (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
The development of digital technology requires villages to transform not only their governance but also their public awareness of digital opportunities and risks. However, the process of digital transformation cannot be separated from the local socio-cultural context. This Community Service (PKM) activity aims to strengthen local wisdom-based transformational leadership as a strategy for dealing with digital dynamics in Pesanggrahan Village, Kutorejo District, Mojokerto Regency. The implementation methods included a situation analysis, program socialization, digital literacy seminars, discussions on Pancasila values, and mentoring for village officials, community leaders, religious leaders, and Karang Taruna youth. The activity results showed an increase in participants' understanding of digital literacy, media ethics, and the relevance of local values, such as cooperation, deliberation, and tolerance, in supporting the village's digital transformation. The community also showed enthusiasm for participating in the development of digital content and technology-based services. This PKM concluded that effective digital transformation requires adaptive, character-based leadership rooted in local cultural values. Collaboration between universities, village governments, and communities is an essential prerequisite for promoting inclusive and sustainable social change.